2014
DOI: 10.1080/02763869.2014.897513
|View full text |Cite
|
Sign up to set email alerts
|

Book Discussion Course: Timely Topics for Medical Students

Abstract: Several library faculty members at the Louisiana State University Health Shreveport Health Sciences Library offered a book discussion course as an elective for first-year medical students. This article provides details on how the librarians developed, taught, and evaluated this elective. The librarians took a team-teaching approach, required the students to read two books, and outlined the criteria for participation. At the end of the course, the students completed an evaluation, commenting on positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…All the studies reviewed reported that the preclinical electives were positively received by students. Of the 37 electives identified, a total of 27 studies employed surveys to assess student impressions of the elective ( 13 22 , 24 32 , 36 , 37 , 39 42 , 44 , 45 , 47 49 ) . Fifteen of the electives used quantitative objective assessments, such as knowledge exams, residency placement results, and validated quantitative scoring rubrics ( 11 , 12 , 15 , 17 , 18 , 24 , 31 33 , 35 , 40 , 41 , 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the studies reviewed reported that the preclinical electives were positively received by students. Of the 37 electives identified, a total of 27 studies employed surveys to assess student impressions of the elective ( 13 22 , 24 32 , 36 , 37 , 39 42 , 44 , 45 , 47 49 ) . Fifteen of the electives used quantitative objective assessments, such as knowledge exams, residency placement results, and validated quantitative scoring rubrics ( 11 , 12 , 15 , 17 , 18 , 24 , 31 33 , 35 , 40 , 41 , 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…While there has been an influx of literature over the last decade on ways to implement IPE learning activities in academic environments [69], an extracurricular activity involving the utilization of a nonfiction book across various professions presents a new IPE learning opportunity. While book discussions have been used many times in health professions education to encourage professionalism [10], cultural competence [11–17], leadership [1415, 1821], empathy and compassion [13, 2226], ethics [12, 2729], spiritual care [30], and other outcomes [13, 19, 31–34], Kilham and Griffiths found no studies in the literature using a standalone book discussion activity for IPE purposes [35].…”
Section: Introductionmentioning
confidence: 99%
“…Books about patient or health care provider experiences allow readers to reflect on the often sensitive or shocking parts of the story in a safe environment when they are emotionally ready [14, 24]. Book discussions present issues in “an environment that encourages the students to share their insights and solutions to patient and professional dilemmas” [26]. This makes an IPE book discussion an ideal activity to allow students to engage with others from different disciplines, while also achieving the definition of IPE as outlined by the World Health Organization [1].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature has found similar suggestions for enhanced student input into discussion materials in a course for medical students. 4 …”
Section: Resultsmentioning
confidence: 99%
“…Discussion courses have been used successfully in a variety of settings, such as in ethics courses [1][2][3] and when bringing together multiple disciplines. 4,5 The main goals of discussion courses align well with the goals of graduate education, where students take responsibility for their own learning and synthesize material beyond simple recall. 6,7 However, like learning to be an independent researcher, effective discussion-based learning demands allocated practice time to communicate expectations for successful discussions.…”
Section: Introductionmentioning
confidence: 94%